An Analisys Of English-Indonesian Translation Of The Film's Sub-Titling Friends - Puspita, Agustin Ira (2004)
This research is entitled: An Analysis of English Indonesian Translation of the Film's Sub-Titling Friends. It is a descriptive study on the development of the language translation, especially in film. Started from the theory that the knowledge translation is reproducing the source language into receptor language in order to delivery the massage. These research studies the phenomena of deviant translation happened in the film sub-titling Friends in the episode "The Halloween Party". Focused on the deviation of translation, this research was to find the numbers of deviation and the factors that may affect the translation to deviate from its original script. Finally, the writer is able to identify the level of appropriateness of the data that is used. Descriptive method was used here, and total sampling technique was employed. Data were taken from the Indonesian translated scrip t of film Friends in the episode of "The Halloween Party" and its original script in English. Data collecting was done by watching the film repeatedly to collect translation deviations in the dialogues (including within it are inappropriate translation and the untranslated words, phrases, clauses, and sentences). The base for judging deviations is the inappropriate translation and the untranslated words, phrases, clauses, and sentences, with exceptions of the use of reduction text. Coding the data according to the determined rules, and then classifying them to the previously determined classifications did the data analyzing. The study shows that there are 314 data in this film, 23 of which indicate the translation deviations. They consist of classification codes A 7 numbers of data of the inappropriate translations and classification codes B 16 numbers of data of the untranslated words, phrases, clauses, and sentences. The translation of the film Friends in the episode "The Halloween Party" is satisfactory considering that less than half of the data indicates translation deviation. This translation is placed in good level of appropriateness considering that its sub-titles is fully observe the type of program, the target of the audience, and the aesthetics of the language. The researcher hopefully that this research will be useful in adding the about film translation. The extra-linguistics elements of a film are very important to consider beside the dialogue itself.